PERANCANGAN DESAIN USER INTERFACE REKAM MEDIS ELEKTRONIK MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) DI LABORATORIUM RME UNIVERSITAS ESA UNGGUL - Haerani, Tita; Kurniawati, Anastasia Cyintia Dewi (Smart Education, 2025)
Abstract: The EMR system in the Esa Unggul University Laboratory supports Health Information Management students but has access limitations. Users can only access the patient registration feature, while other features require a license, which hampers the learning process. The EMR UI design is a fundamental step in system development. The UI design method used in this study is User-Centered Design (UCD), producing 10 key features including registration, initial nursing assessment, examination, laboratory, radiology, pharmacy, cashier, coding, and reporting. Design evaluation, using Heuristic Evaluation (HE), involved 4 evaluators. The severity score of 1.3, categorized as a